2018
DOI: 10.1088/1475-7516/2018/10/040
|View full text |Cite
|
Sign up to set email alerts
|

Magnetogenesis by non-minimal coupling to gravity in the Starobinsky inflationary model

Abstract: The R 2 term in the Starobinsky inflationary model can be regarded as a leading quantum correction to the gravitational effective action. We assume that parity-preserving and parity-violating (axial) non-minimal couplings between curvature and electromagnetic field are also present in the effective action. In the Einstein frame, they turn into non-trivial couplings of the scalaron and curvature to the electromagnetic field. We make an assessment of inflationary magnetogenesis in this model. In the case of pari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…One may argue that in Ref. [47] the authors show magnetogenesis is not possible because of the strong back reaction of the produced fields on the inflation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may argue that in Ref. [47] the authors show magnetogenesis is not possible because of the strong back reaction of the produced fields on the inflation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for back-reaction problem in Ref. [47] is, the form of potential due to flatness of the Starobinsky potential. Due to flatness of Starobinsky potential ,the coupling function changes very slowly during inflation so that the form of the power spectrum of electromagnetic field in the amplification domain is not essentially modified with respect to to the vacuum case [47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the backreaction of EM fields can modify the inflaton dynamics, change the Universe expansion, and make an impact on the spectrum of primordial perturbations. In our previous work [38], we considered the case of kinetic coupling between the scalar inflaton field and the EM field introduced by Ratra [33] and revisited many times in the literature arXiv:1907.10443v2 [astro-ph.CO] 19 Sep 2019 [37,[39][40][41][42][43][44][45][46][47] and showed that the backreaction of generated electric fields is indeed very important because it strongly suppresses magnetogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…whereF μν = 1 2 μν αβ F αβ is the Hodge dual of the electromagnetic strength tensor F μν , and I and f are non-trivial functions of the cosmological time due to their possible dependence on the background fields such as the inflaton or the metric curvature. In [43], we have shown how such coupling between the curvature and inflaton can arise as a result of quantum corrections in the Starobinsky inflationary model [55]. But we will not specify such couplings here, making our consideration general and model independent.…”
Section: Introductionmentioning
confidence: 99%